Efektivitas Belanja Daerah dalam Pembangunan Wilayah Adat La Pago di Papua - Riani, Ida Ayu Purba; Hafizrianda, Yundy (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2026)
This study generally aims to analyze the level of effectiveness of regional spending on the development of macro- and socio-economic performance in the Wilayah Adat La Pago. The macro-socio-economic performance measured is economic growth, the Human Development Index (HDI), and the poverty rate. There are two tools used to measure it: discrete elasticity and continuous elasticity. Referring to the results of the continuous elasticity analysis, it was found that regional spending in the Wilayah Adat La Pago as a whole is effective in driving economic growth. An increase in regional spending of 1% is able to increase the Gross Domestic Regional Product (GDRP) by 0.69% on average. Although regional spending has a significant effect on increasing HDI, its level of effectiveness is very low. An increase in regional spending of 1% is only able to increase HDI by 0.19%. Regional spending also has a significant effect on reducing poverty, but its level of effectiveness is very low. An increase in regional spending of 1% is only able to reduce the poverty rate by 0.13%. Specifically, this analysis also identified that Nduga, Lanny Jaya, and Yalimo Regencies have the best performance in making regional spending effective to drive economic growth. Then, for the effectiveness of regional spending on the Human Development Index, only Nduga Regency is indicated as the best. And finally, in reducing poverty, there are two regencies, namely Yalimo and Puncak Jaya. Keywords: Regional Spending, Effectiveness, Elasticity